2017
DOI: 10.1016/j.applanim.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Exposing avian embryos to light affects post-hatch anti-predator fear responses

Abstract: Environmental stimuli present during incubation can impact the behavior of birds post-hatch. To determine the effect of exposing broiler chicken embryos to light on fearrelated behavior post-hatch, we conducted two experiments in which we incubated eggs under various light schedules, and then measured fear responses when the chickens (N = 720) were 3-6 wk of age. In Expt. 1, the incubation photoperiods were 0L:24D, 12L:12D, and 24L:0D, and tonic immobility (TI) and inversion (INV) tests were administered. In E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
(35 reference statements)
3
26
0
Order By: Relevance
“…This result was confirmed by Dharmaretnam and Rogers [77], who additionally found that the dark-incubated chicks made more distress calls during the dual task than did the light-exposed chicks. This was also confirmed more recently by Archer and Mench [78], who found that the effect extends to at least six weeks post-hatching. Since monitoring for predators while searching for food is a common demand in the natural environment, the results of these experiments demonstrate a survival-relevant function of having a lateralized brain.…”
Section: Strength Of Lateralization and Performance In Birdssupporting
confidence: 69%
“…This result was confirmed by Dharmaretnam and Rogers [77], who additionally found that the dark-incubated chicks made more distress calls during the dual task than did the light-exposed chicks. This was also confirmed more recently by Archer and Mench [78], who found that the effect extends to at least six weeks post-hatching. Since monitoring for predators while searching for food is a common demand in the natural environment, the results of these experiments demonstrate a survival-relevant function of having a lateralized brain.…”
Section: Strength Of Lateralization and Performance In Birdssupporting
confidence: 69%
“…Compared to the dark-incubated chicks, all of the light-exposed chicks were less fearful on all of the measures, and the least fearful chicks were those exposed to light throughout incubation. In a subsequent study, Archer and Mench [91] confirmed the role of light exposure in reducing fear responses and recommended 12 hours of light exposure daily throughout incubation to reduce fear and improve welfare of chicks. Even as little as 6 hours of light per day was sufficient to reduce fear on some tests.…”
Section: Exposure To Light During Incubation Of Birds Raised In Flockmentioning
confidence: 88%
“…Whether or not this effect of light on post-hatching behaviour relates directly to the effect of light exposure on the development of lateralization has yet to be determined. However, differences in lateralization are likely to be involved, and Archer and Mench [91] did show effects of the light exposure on lateralization in tests of turning bias.…”
Section: Exposure To Light During Incubation Of Birds Raised In Flockmentioning
confidence: 96%
See 1 more Smart Citation
“…As birds are oviparous, the incubation conditions can be modified in order to study the impact of environmental challenges or stressors during embryogenesis, thus reducing the impact of the maternal influence. Incubation parameters such as temperature [2], light [3] or noise [4] are known to impact development and behavior. In a context of climate change, with an increase of global average temperature and the occurrence of extreme heatwaves [5], numerous studies have reported the utilization of the thermal-manipulation (TM) of eggs during the incubation period to improve the later-life heat tolerance of chickens [2,[6][7][8][9][10][11][12][13][14][15][16] and turkeys [17,18] or to modify muscle development in ducks [19][20][21].…”
Section: Introductionmentioning
confidence: 99%